2008
DOI: 10.1021/jp805421g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Potential in Nematogenic 6CHBT

Abstract: Pressure-volume-temperature (PVT) measurements were carried out on the nematic liquid crystal 4(trans-4′-n-hexylcyclohexyl)isothiocyanatobenzene (6CHBT). In combination with previous dielectric relaxation measurements at elevated pressure and new measurements extending to GHz frequencies, the characteristics of the anisotropic interaction potential were determined. The thermodynamic potential parameter, Γ, which measures the variation of the interaction energy with volume, equals 5.03 ( 0.06, with a barrier he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…This is close to the reported for other smectogens, whereas the N-Iso transition is usually associated with larger values of (see Table 1). For comparison, included in Table 1 are the potential parameter γ derived from thermodynamic scaling of the longitudinal relaxation times [2,16,17,19,20,[35][36][37][38].…”
Section: Analysis Of the Clearing Linementioning
confidence: 99%
“…This is close to the reported for other smectogens, whereas the N-Iso transition is usually associated with larger values of (see Table 1). For comparison, included in Table 1 are the potential parameter γ derived from thermodynamic scaling of the longitudinal relaxation times [2,16,17,19,20,[35][36][37][38].…”
Section: Analysis Of the Clearing Linementioning
confidence: 99%
“…Fig. 5 shows examples of the volume-temperature plots at constant τ || and constant P for two LC substances in the nematic phase: pentyl-cyanobiphenyl (5CB) [22] and 4(trans-4′-n-hexylcyclohexyl)isothiocyanatobenzene (6CHBT) [23]. The obtained expansivity coefficients are listed in Table 1, together with the data for other LCs.…”
Section: Low Frequency Relaxation Process In Lcsmentioning
confidence: 99%
“…The former is considerably larger, as found for other LC materials [2,[5][6][7][8][9][10][11][12]24,25]. Figure 6 compares the two quantities for the N phase of 8OCB and 8CB [26].…”
Section: Resultsmentioning
confidence: 52%
“…It has been shown that the scaling relation, Equation (2), originally proposed for glass-forming liquids and polymers ( [23,29] and references therein), is applicable to the longitudinal relaxation times in various types of LCs [5][6][7][8][9][10][11][12]. As shown in Figure 8 (lower curve), the values of τ in Figures 4 and 5 superpose to form a master curve when plotted versus the scaling variable TV γ , with the value γ = 4.2 the same as determined for 8CB [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation